2009
DOI: 10.1073/pnas.0810063106
|View full text |Cite
|
Sign up to set email alerts
|

Somatosensory function in speech perception

Abstract: Somatosensory signals from the facial skin and muscles of the vocal tract provide a rich source of sensory input in speech production. We show here that the somatosensory system is also involved in the perception of speech. We use a robotic device to create patterns of facial skin deformation that would normally accompany speech production. We find that when we stretch the facial skin while people listen to words, it alters the sounds they hear. The systematic perceptual variation we observe in conjunction wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
187
4
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 166 publications
(211 citation statements)
references
References 26 publications
(56 reference statements)
19
187
4
1
Order By: Relevance
“…The reported instances extend from somatosensory inputs to the cochlear nucleus through to bidirectional interactions between auditory and somatosensory cortex (16)(17)(18)(19)(20)(21)(22). There is also evidence that somatosensory inputs affect auditory perceptual function including cases involving speech (8,23,24). The present example of somatosensory-auditory interaction is intriguing because subjects do not normally receive somatosensory inputs in conjunction with the perception of speech sounds but rather with their production.…”
Section: Discussionmentioning
confidence: 78%
“…The reported instances extend from somatosensory inputs to the cochlear nucleus through to bidirectional interactions between auditory and somatosensory cortex (16)(17)(18)(19)(20)(21)(22). There is also evidence that somatosensory inputs affect auditory perceptual function including cases involving speech (8,23,24). The present example of somatosensory-auditory interaction is intriguing because subjects do not normally receive somatosensory inputs in conjunction with the perception of speech sounds but rather with their production.…”
Section: Discussionmentioning
confidence: 78%
“…The experimental setup with the EEG system is represented in Figure 1. The details of the somatosensory stimulation device have been described in the previous studies 1,7,[12][13][14] . Briefly, two small plastic tabs (2 cm wide and 3 cm height) are attached with double-sided tape to the facial skin.…”
Section: Somatosensory Stimulationmentioning
confidence: 99%
“…Recent results suggest that somatosensory processes contribute to perception as well as production. For example, the identification of speech sounds is altered when a robotic device stretches the facial skin as participants listen to auditory stimuli 1 . Air puffs to the cheek that coincide with auditory speech stimuli alter participants' perceptual judgments 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Among the vast number of active learning architectures, 191 this paper considers the exploration architecture proposed 192 In [28], a robotic device able to generate patterns of facial 246 skin deformation related to certain speech productions was 247 used. The results showed that when the facial skin is stretched 248 whilst subjects are listening to words, the sounds they hear are 249 altered.…”
mentioning
confidence: 99%
“…Furthermore, the fact that CB also emerges 242 in deaf infants suggests that somatosensory feedback must play 243 a more relevant role during the prelinguistic vocal development 244 in infants [27]. In [28], a robotic device able to generate patterns of facial 246 skin deformation related to certain speech productions was 247 used. The results showed that when the facial skin is stretched 248 whilst subjects are listening to words, the sounds they hear are 249 altered.…”
mentioning
confidence: 99%